اتجاهات أساتذة التعليم الثانوي نحو استخدام استراتيجيات التعلم التعاوني في عملية التدريس. (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص: هدفت هذه الدراسة إلى التعرف على اتجاهات أساتذة التعليم الثانوي نحو استخدام استراتيجيات التعلم التعاوني في عملية التدريس، وتم الاعتماد على المنهج الوصفي الاستكشافي ولتحقيق أغراض البحث قام الباحثان بتصميم أداة الدراسة (الاستبيان) وتطبيقها على أساتذة التعليم الثانوي بمدينة عين الحجل بالمسيلة. وتكونت عينة الدراسة من 97 أستاذا.وبعد تطبيق أداة الدراسة تم التوصل إلى النتائج التالية:-     استخدام استراتيجيات التعلم التعاوني يسهم في تشجيع التعاون والتفاعل بين التلاميذ.-     اتجاهات أساتذة التعليم الثانوي نحو استخدام استراتيجيات التعلم التعاوني في التدريس إيجابية.-     لا توجد فروق ذات دلالة إحصائية بين متوسط إجابات أساتذة التعليم الثانوي في الاتجاه نحو استخدام استراتيجيات التعلم التعاوني في التدريس تعزى لمتغير الجنس.-     لا توجد فروق ذات دلالة إحصائية بين متوسط إجابات أساتذة التعليم الثانوي في الاتجاه نحو استخدام استراتيجيات التعلم التعاوني في التدريس تعزى لمتغير التخصص.كلمات دالة: اتجاهات, أساتذة تعليم ثانوي, استراتيجية, تعليم تعاوني.  Abstract: This study aimed to identify the attitudes of secondary education teachers towards the use of cooperative learning strategies in the teaching process, and the exploratory descriptive approach was relied upon to achieve the research objectives. The researchers designed the study tool (the questionnaire) and applied it to secondary education professors in the city of Ain al-Hajl in M'sila. The study sample consists of 97 professors. After applying the study tool, the following results were reached:- The use of cooperative learning strategies contribute to encouraging cooperation and interaction between students.- The attitudes of secondary education teachers towards the use of cooperative learning strategies in teaching are positive.- There are no statistically significant differences between the average answers of secondary education teachers in the trend towards the use of cooperative learning strategies in teaching due to the gender variable.- There are no statistically significant differences between the average of secondary education teachers ’answers in the trend towards the use of cooperative learning strategies in teaching due to the specialization variableKey words: Directions, teachers of secondary education, strategy, cooperative education